ANALISIS NILAI DAKWAH DALAM TARI SAMAN - Amalia; Halida (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2024)
Saman dance has many uniqueness both from the movements and messages conveyed through verse. This study aims to examine the history and values of da'wah contained in Saman Dance, then the focus of research is the values of da'wah contained in Saman Dance verses. In this study, the author is interested in understanding how Saman Dance plays a role in spreading da'wah values in the Gayo tribal community by using qualitative descriptive research methods through literature study analysis techniques, data reduction, data presentation, and conclusions from various articles and research data source books. By exploring the verses of Saman Dance, this study highlights some of the values of da'wah in Saman Dance. First, there are verses of praise to Allah and greetings to the audience as a form of respect. Second, there is a moral message conveyed through poetry, including the values of togetherness, courtesy, and gratitude. Third, there is a call to protect and preserve nature, in line with Islamic teachings on harmony between humans and their environment. Fourth, there is an encouragement to keep trying in the face of adversity.